Verifying vehicle control systems by using process calculi. (2016) - Ciobanu, Gabriel; Rotaru, Armand Stefan
The paper deals with the safety of car control systems in which vehicle-to-vehicle interactions are described in a modular and compositional manner. Such a description simplifies a complex verification process, which involves control decisions regarding acceleration, deceleration, lane switching and braking distance. We focus on the problem of adjusting vehicle speed in order to maintain a proper distance between vehicles on the same lane. The components of the control system are represented as processes in the process algebra Communicating Sequential Processes, and the compositional parallel operator is used to describe the whole system. Safety properties are formally verified by employing the Concurrency Workbench of the New Century tool.